2011
DOI: 10.1523/jneurosci.4771-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility of the Ligand-Binding Domain Dimer in Kainate Receptor Gating and Desensitization

Abstract: AMPA-and kainate (KA)-selective ionotropic glutamate receptors (iGluRs) respond to agonist by opening (gating), then closing (desensitizing) in quick succession. Gating has been linked to agonist-induced changes within the ligand-binding domain (LBD), and desensitization to rearrangement of a dimer formed by neighboring LBDs. To explore the role of dimer conformation in both gating and desensitization, we compared the conformational effects of two kainate receptor mutants. The first, GluK2-D776K, blocks desens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 40 publications
(73 reference statements)
6
62
0
Order By: Relevance
“…Two such GluA2-like dimeric structures of GluK1 (Mayer et al, 2006;Unno et al, 2010) and also two of GluK2 (Chaudhry et al, 2009;Nayeem et al, 2011) have been determined in complex with glutamate. However, in other structures with glutamate either monomers (Mayer, 2005;Unno et al, 2010) or a different dimer (Mayer, 2005;Naur et al, 2005) were seen.…”
Section: Dimerization Of the Gluk3 Ligand Binding Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Two such GluA2-like dimeric structures of GluK1 (Mayer et al, 2006;Unno et al, 2010) and also two of GluK2 (Chaudhry et al, 2009;Nayeem et al, 2011) have been determined in complex with glutamate. However, in other structures with glutamate either monomers (Mayer, 2005;Unno et al, 2010) or a different dimer (Mayer, 2005;Naur et al, 2005) were seen.…”
Section: Dimerization Of the Gluk3 Ligand Binding Domainmentioning
confidence: 99%
“…It is also possible that the dimer observed is merely a consequence of crystal packing. However, it is known that introducing mutations in dimer interfaces might lead to significant and unexpected effects in receptor function (Nayeem et al, 2011), so a functional role of the observed dimer versus crystal packing effects cannot be completely ruled out.…”
Section: Dimerization Of the Gluk3 Ligand Binding Domainmentioning
confidence: 99%
“…No similar drugs have been reported for kainate receptors, although their disclosure likely remains only a matter of time. However, crystal structures for LBD dimer assemblies of GluK1, GluK2 and GluD2 reveal novel binding sites for Na + , Ca 2+ and Cl − ions (84, 120123), which act as counter charges at polar sites on the dimer interface, thereby increasing LBD dimer stability and reducing desensitization (124). …”
Section: Novel Allosteric Modulatorsmentioning
confidence: 99%
“…
Figure 1.Apical interactions within GluK2 LBD dimer. ( a ) The GluK2 WT LBD dimer (PDB code 2 xxr ) [7] showing ligand (black), domains D1 and D2, the twofold axis and the Na + and Cl − ions (purple and green, respectively). Key D1:D1 interactions are shown inset on protomer B; pink surface from data in reference [8] and grey surface from this study.
…”
Section: Introductionmentioning
confidence: 99%